If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 105 + -2x = 16x + 23 Reorder the terms: 105 + -2x = 23 + 16x Solving 105 + -2x = 23 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 105 + -2x + -16x = 23 + 16x + -16x Combine like terms: -2x + -16x = -18x 105 + -18x = 23 + 16x + -16x Combine like terms: 16x + -16x = 0 105 + -18x = 23 + 0 105 + -18x = 23 Add '-105' to each side of the equation. 105 + -105 + -18x = 23 + -105 Combine like terms: 105 + -105 = 0 0 + -18x = 23 + -105 -18x = 23 + -105 Combine like terms: 23 + -105 = -82 -18x = -82 Divide each side by '-18'. x = 4.555555556 Simplifying x = 4.555555556
| 3x-2=-29 | | 115-3x+5x=11 | | 2[a+7]-7=9 | | 1+4x=-x-5 | | 2x+20=12x-60 | | 6x+62=10+14 | | 2t^3-9t^2-27=0 | | x^2+3x=117 | | 171-6x=30x+15 | | 34y+5=345 | | (8*20)2+(8*13)2-(5*3)3-(7*2)=x | | N*3=38 | | 101-6x=21x+23 | | 0=0.02d^2-2.6d+66.5 | | 4x^2-6x-12=0 | | -5+x+3=7 | | 10-2x-6=-x+5 | | (8*20)2+(8*13)2-(5*3)3-(7*2)= | | 50-2x=16x+16 | | 6x+6=106-10x | | 12x^2+19x=-5 | | (8*20)2+(8*13)2=X | | -7-9w=-7w-10 | | -5-6=-4x-(x+6) | | 9-x-2x=0 | | -5-6=-4-(x+6) | | (8*20)2=x | | N-15=22 | | x+3=40 | | 952=12d+28 | | 7x-4-3x=4x+8 | | -(7x-2)+5=3 |